Otis Elevator Exhibit, the Highest at the Fair - The Sky-Ride
The eight Otis Automatic Signal-Control "Sky-Ride" Elevators carried 6,000,000 passengers in five and one-half months last year - a new record for intensive elevator service. When you visit the fair, don't fail to go behind the scenes and see these elevator machines in operation.